MEASUREMENT OF INFUSION FLOW RATE USING A DROPLET SENSOR BASED ON ARDUINO UNO - Ihsan, Khairul; Nanda Setiadi, Rahmondia; Taer, Erman; Umar, Lazuardi (JOURNAL ONLINE OF PHYSICS, 2023)
A research has been conducted to help the medical staff in the hospital. The purpose of this study is to calculate and regulate the infusion flow rate of the infusion into the patient's body. This research uses an experimental method. The liquid released from the infusion is converted into droplets, which are then detected by the LM393 optocoupler sensor, which consists of three sensors arranged around the detection area by emitting infrared light through a transmitter to detect the shadow of the droplet so that the signal is received by the receiver of the optocoupler sensor. Which is processed with the Arduino Uno microcontroller. The Arduino Uno provides the results received from the sensor and coded using the Arduino IDE software to be displayed on a 16x2-character Liquid Crystal Display (LCD). The sample used in this study was Sodium Chloride (NaCl). The calibration tools performed were droplet sensor test, servo motor test, and Real Time Clock (RTC) DS3231 module test. The results of the detection in the droplet sensor configuration showed a high degree of accuracy, with an error value of 2.414%. so that this research can be implemented in the detection and appropriate management of infusion flow rates. The current testing being carried out is still on a laboratory scale. However, in the future, this system can be developed to monitor infusions in real-time over a longer period of time and using more complex data processing functions.